LAN NETWORK WORKING SYSTEM ON PT. USAHA SISTEM INFORMASI - Franz Parman; Aqwam Rosadi Kardian, Ir, MMSI. (Jurnal Sistem Informasi, 1998)
LAN to access the network data security system requires a very secure, so not everyone is authorized to update existing data. to be able to support LAN networking, in order to provide efficiency and effectiveness of work in data processing. LAN network in order to manufacture a very large cost much less to use IBM's Token Ring network system. because it requires equipment that its quality is very good.